Efficacy of Endoscopic Sutured Gastroplasty on Diabetes Mellitus Type 2—A Systematic Review - Fenna M. M. Beeren; Mitchell J. R. Harker; Arianne C. vanBon; Marcel J. M. Groenen; Peter D. Siersema (Endocrinology, Diabetes & Metabolism)
ABSTRACT Introduction Endoscopic sutured gastroplasty (ESG) is one of the currently available endoscopic techniques that mimics bariatric surgery. Although the efficacy of ESG on weight loss has repeatedly been demonstrated, its effect on diabetes mellitus type 2 (T2DM) related outcomes is not yet fully clear. Methods We conducted a systematic review summarising the efficacy of ESG on T2DM. Therefore, PubMed, Embase and Cochrane library were searched for studies evaluating the effect of ESG on T2DM. Both prospective and retrospective studies, published in the English language, were included. Two reviewers independently screened all studies. The primary objectives were T2DM remission rate, decrease in glucose‐lowering medication and decrease in HbA1c. Results A total of 16 studies including 760 patients with (pre)diabetes were included. Overall, T2DM‐related outcomes after ESG improved in 303 of 599 patients (50.6%) (including tapering dose of insulin and/or improvement of HbA1c/fasting glucose). Remission rates of T2DM were reported in 6/11 studies and seen in 89 of 155 (57.0%) patients after 6–36 months. Conclusion This systematic review on the efficacy of ESG on T2DM suggests that ESG is able to improve diabetes‐related outcomes in approximately half of treated patients, with T2DM remission rates in more than half of them.